Rapid Detection of Multi-Resistance Strains Carrying mcr-1 Gene Using Recombinase-Aided Amplification Directly on Clinical Samples - Fan, Zheng; Feng, Yanling; Xu, Wenjian; Feng, Junxia; Yan, Chao; Fu, Tongtong; Zhao, Hanqing; Cui, Jinghua; Gan, Lin; Liu, Shiyu; Du, Shuheng; Zhang, Rui; et al. (Frontiers in Microbiology, 2022)
With the increasingly severe problem of bacterial resistance, colistin, as the last line of defense, has attracted attention again. Mobile colistin resistance (mcr-1) gene is involved in the horizontal transmission of colistin resistance in Gram-negative bacteria(GNB), which is a serious threat to human health. Therefore, rapid detection of mcr-1 gene presence in clinical samples is crucial. In this study, a Recombinase-aided amplification（RAA） method for mcr-1 was successfully constructed, with sensitivity of 20 copies/reaction. In addition, amplification signal could only be detected in the strain containing mcr-1 gene among 14 different bacterial species. The method was then used to test a total of 672 clinical samples from a pediatric hospital in Beijing. Five strains harbored mcr-1 genes were isolated from mcr-1-positive clinical samples and identified as Escherichia coli. Multi-locus sequence typing (MLST) analysis showed that the five E. coli belonged to different ST types. Notably, the mcr-1 gene from the isolates could be transferred conjugately to the recipient strain E. coli J53, with highest transfer efficiency up to 57%-58%, suggesting that the mcr-1 gene was located on the plasmid. These findings showed that the RAA assay has potential to be a rapid and sensitive mcr-1 gene screening test for clinical samples, and mcr-1 could be transmitted vertically and horizontally between and within bacterial species in a plasmid-mediated manner.